2000
DOI: 10.1243/0954407001527268
|View full text |Cite
|
Sign up to set email alerts
|

Study on the performance and emissions of a compression ignition engine fuelled with dimethyl ether

Abstract: The paper presents the research results of a light-duty direct injection diesel engine operating on dimethyl ether (DME). The eects of the main parameters of the combustion system, such as plunger diameter, nozzle type, fuel delivery advance angle, protruding distance of the nozzle tip from the bottom plane of the cylinder head and swirl ratio, on the performance of the DME engine are investigated. The indicator diagrams are taken after optimizing the combustion system and characteristics of combustion and emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…Dimethoxymethane (DMM) is the smallest member of the family of oxygenated methyl ethers (OMEs). OMEs (CH 3 −O−(CH 2 −O) n −CH 3 ) turn out to be beneficial additives for diesel fuels: They reduce soot [3,2,29], noise [47] and increase the efficiency by altering viscosity, lubricity, and cetane number [18]. Especially their positive influence onto the soot-NO x tradeoff [38,50] makes them attractive in the context of current pollutant challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Dimethoxymethane (DMM) is the smallest member of the family of oxygenated methyl ethers (OMEs). OMEs (CH 3 −O−(CH 2 −O) n −CH 3 ) turn out to be beneficial additives for diesel fuels: They reduce soot [3,2,29], noise [47] and increase the efficiency by altering viscosity, lubricity, and cetane number [18]. Especially their positive influence onto the soot-NO x tradeoff [38,50] makes them attractive in the context of current pollutant challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional diesel, DME fueled engines generate less noise, and emit fewer pollutants (particulates, NO x, hydrocarbons, and CO). However, it has a lower energy density than diesel, so a double-sized tank is needed to maintain similar travel range [286]. DME engines have certain special requirements: a vapor pressure of 510 kPa at 25°C, low viscosity and lubricity, with compressibility rising near full load conditions.…”
Section: Synthesis Of Oxygenatesmentioning
confidence: 99%
“…Two direct injection single diesel engines were used in the study. The DME engine was modi®ed from a diesel engine with some change in the parameters (see Table 1) on the basis of the authors' earlier experimental studies [4,5]. A DME engine with these parameters will achieve optimum performance.…”
Section: Test Engine and Fuel Propertiesmentioning
confidence: 99%
“…Their results show that the engine can achieve ultralow emission without fundamental change to the combustion system. Huang et al [4,5] investigated the combustion and emission characteristics in a compression ignition engine with DME and found that the DME engine has high thermal eciency, short premixed combustion and fast diusion combustion, making it possible to achieve low-noise, smoke-free combustion. Kajitani et al [6] studied the DME engine with delay in the injection time to reduce both smoke and NO x .…”
Section: Introductionmentioning
confidence: 99%